Constraints on the unitarity triangle angle γ from Dalitz plot analysis of B0→DK+π- decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Physical review, 2016)
The first study is presented of CP violation with an amplitude analysis of the Dalitz plot of B0→DK+π− decays, with D→K+π−, K+K−, and π+π−. The analysis is based on a data sample corresponding to 3.0 fb−1 of pp collisions collected with the LHCb detector. No significant CP violation effect is seen, and constraints are placed on the angle γ of the unitarity triangle formed from elements of the Cabibbo-Kobayashi-Maskawa quark mixing matrix. Hadronic parameters associated with the B0→DK∗(892)0 decay are determined for the first time. These measurements can be used to improve the sensitivity to γ of existing and future studies of the B0→DK∗(892)0 decay.
*LHCb Collaboration: R. Aaij, P. D'Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, U. Uwer, M. Vesterinen, A. Zhelezov [und 705 weitere Personen]
Im Titel sind die Zahl 0 und die Zeichen + und - hochgestellt
Gesehen am 10.07.2020